Bloodstream infections due to Carbapenem-Resistant Enterobacteriaceae in hematological patients: assessment of risk factors for mortality and treatment options - Lining Zhang; Sisi Zhen; Yuyan Shen; Tingting Zhang; Jieru Wang; Jia Li; Qingsong Lin; Zhijian Xiao; Yizhou Zheng; Erlie Jiang; Mingzhe Han; Jianxiang Wang; et al. (BMC, 2023)
Abstract Purpose Bloodstream infection (BSI) caused by Carbapenem-Resistant Enterobacteriaceae (CRE) are associated with poor outcomes in hematological patients. The aim of this study was to identify risk factors for mortality and evaluate the value of epidemiological feature of carbapenemases in guiding antimicrobial treatment options. Methods Hematological patients with monomicrobial CRE BSI between January 2012 and April 2021 were included. The primary outcome was all-cause mortality 30 days after BSI onset. Results A total of 94 patients were documented in the study period. Escherichia coli was the most common Enterobacteriaceae, followed by Klebsiella pneumoniae. 66 CRE strains were tested for carbapenemase genes, and 81.8% (54/66) were positive, including NDM (36/54), KPC (16/54), IMP (1/54). Besides, one E. coli isolate was found to express both NDM and OXA-48-like genes. Overall, 28 patients received an antimicrobial treatment containing ceftazidime-avibactam (CAZ-AVI), of which 21 cases were combined with aztreonam. The remaining 66 patients were treated with other active antibiotics (OAAs). The 30-day mortality rate was 28.7% (27/94) for all patients, and was only 7.1% ((2/28) for patients treated with CAZ-AVI. In multivariate analysis, the presence of septic shock at BSI onset (OR 10.526, 95% CI 1.376-76.923) and pulmonary infection (OR 6.289, 95% CI 1.351-29.412) were independently risk factors for 30-day mortality. Comparing different antimicrobial regimens, CAZ-AVI showed a significant survive benefit than OAAs (OR 0.068, 95% CI 0.007-0.651). Conclusion CAZ-AVI-containing regimen is superior to OAAs for CRE BSI. As the predominance of blaNDM in our center, we recommend the combination with aztreonam when choose CAZ-AVI.